Propagation Studies in Free Space Using RZ and NRZ Optical Links Under Atmospheric Turbulence - Sony, K; Sarat Kumar, K; CH. Sri Kavya, K (International Journal of Engineering and Technology, 2018)
Free Space optics provides a solution for the growing bandwidth requirements of internet applications. It offers a better solution for bottleneck problems of connectivity but faces a major problem due to atmospheric effects such as Haze, Fog, Snow, Rain. The work modeledÂ here deals about providing a system designed for the FSO link which can offer efficientÂ transmission of data up to 3km considering the influence of Fog while transmission with better Quality factor and minimum Bit error RateÂ and also does a comparative analysis of two system designs of FSO with a single source and with array of lasers at operating wavelength of 850 nmÂ using the Wavelength Division MultiplexingÂ with both RZ and NRZ Formats.Â Â